2010
DOI: 10.1042/bj20101287
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel species-selective agonists of the G-protein-coupled receptor GPR35 that promote recruitment of β-arrestin-2 and activate Gα13

Abstract: The poorly characterized G-protein-coupled receptor GPR35 has been suggested as a potential exploratory target for the treatment of both metabolic disorders and hypertension. It has also been indicated to play an important role in immune modulation. A major impediment to validation of these concepts and further study of the role of this receptor has been a paucity of pharmacological tools that interact with GPR35. Using a receptor-β-arrestin-2 interaction assay with both human and rat orthologues of GPR35, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(167 citation statements)
references
References 26 publications
4
162
1
Order By: Relevance
“…mFFA4-Arrestin 3 Interaction Assay. Arrestin 3 recruitment to mFFA4 was assessed using a bioluminescence resonance energy transfer (BRET) assay (Jenkins et al, 2010;Butcher et al, 2014;Hudson et al, 2014;MacKenzie et al, 2014). Briefly, human embryonic kidney 293T (HEK293T) cells were cotransfected with arrestin 3-Renilla luciferase and eYFP-tagged receptor plasmids in a 1:4 ratio using polyethyleneimine.…”
Section: Methodsmentioning
confidence: 99%
“…mFFA4-Arrestin 3 Interaction Assay. Arrestin 3 recruitment to mFFA4 was assessed using a bioluminescence resonance energy transfer (BRET) assay (Jenkins et al, 2010;Butcher et al, 2014;Hudson et al, 2014;MacKenzie et al, 2014). Briefly, human embryonic kidney 293T (HEK293T) cells were cotransfected with arrestin 3-Renilla luciferase and eYFP-tagged receptor plasmids in a 1:4 ratio using polyethyleneimine.…”
Section: Methodsmentioning
confidence: 99%
“…Although GPR35 is indicated to be a receptor responsive to the endogenously produced tryptophan metabolite kynurenic acid (Wang et al, 2006), lack of convergence on this issue has resulted in a number of efforts to identify surrogate agonist ligands that might be used to help further define the roles of this receptor. Although a number of such ligands have been identified (Taniguchi et al, 2006;Jenkins et al, 2010;Zhao et al, 2010;Deng et al, 2012;Funke et al, 2013;Neetoo-Isseljee et al, 2013), many of these are either of modest potency and/or display markedly different potency at human and rodent orthologs of GPR35 (Jenkins et al, 2010;Funke et al, 2013;Neetoo-Isseljee et al, 2013). This has posed challenges both in efforts to define the orthosteric binding pocket of the receptor and to use rodents and cell lines derived from such animals to further explore the function of GPR35.…”
Section: Introductionmentioning
confidence: 99%
“…The antiasthma and antiallergic agents cromolyn disodium (Jenkins et al, 2010;Yang et al, 2010) and nedocromil sodium (Yang et al, 2010) were recently shown to act as moderately potent agonists of GPR35. These ligands are both di-acids with marked mirror image symmetry (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Niflumic acid has also been found to be an activator of GPR (G-protein coupled receptor) 35, a protein implicated in a number of conditions including inflammatory pain, asthma, heart disease, cancer, and metabolic diseases, and regarded as a promising therapeutic target. 51 Preclinical studies have shown that morniflumate has marked anti-inflammatory activity, comparable with niflumic acid.…”
Section: Pharmacodynamic Profilementioning
confidence: 99%